Laparoscopic-assisted repair of Morgagni hernia in children - Osama A. Bawazir; Anies Mahomed; Amira Fayyad; Elham Bagaryn; Abdullah Bawazir; Rahaf Mandora (SpringerOpen, 2020)
Abstract Background Morgagni hernia (MH) is a rare diaphragmatic hernia with nonspecific symptoms and variable presentation. MH is managed surgically via laparotomy or a thoracotomy. Recently, laparoscopy was described for the repair of MH. The objective of this study is to report our institutional experience in laparoscopic repair of MH in infants and children. Results Twenty-five patients with MH were included; 17 of them were males (68%). Their median age at the time of diagnosis was 18 months. Sixteen patients (64%) presented with a recurrent chest infection. MH was on the right side in 8 patients, left side in 2, and central in 12, and 3 patients had bilateral hernias. Eleven patients (44%) had congenital heart disease, 10 (40%) had Down's syndrome, and 2 (4%) had malrotation of the bowel. The median size of the hernia defect was 3 × 3.5 cm2, and the most common content was the colon (n = 19). One patient with Down's syndrome developed recurrence and underwent open repair. The median operative time was 95 min. The postoperative recovery was uneventful, and the average postoperative stay was 3 days. The median follow-up was 4.5 years, and there was no reported mortality. Conclusions Morgagni hernia is commonly associated with other congenital anomalies. Laparoscopic repair of Morgagni hernia in children is feasible with excellent postoperative outcomes.